Global miRNA expression reveals novel nuclear and mitochondrial interactions in Type 1 diabetes mellitus - Ferraz, Rafaella Sousa; Santos, Lucas Cauê Bezerra; da-Silva-Cruz, Rebecca Lais; Braga-da-Silva, Cintia Helena; Magalhães, Leandro; Ribeiro-dos-Santos, Arthur; Vidal, Amanda; Vinasco-Sandoval, Tatiana; Reis-das-Mercês, Laís; Sena-dos-Santos, Camille; Pereira, Adenilson Leão; Silva, Lilian Souza D’Albuquerque; et al. (Frontiers in Endocrinology, 2022)
Background Considering the potential role of miRNAs as biomarkers and their interaction with both nuclear and mitochondrial genes, we investigated the miRNA expression profile in type 1 diabetes (T1DM) patients, including the pathways in which they are involved considering both nuclear and mitochondrial functions. Methods We analyzed samples of T1DM patients and control individuals (normal glucose tolerance) by high throughput miRNA sequencing (miRNome). Next, five miRNAs – hsa-miR-26b-5p, hsa-let-7i-5p, hsa-miR-143-3p, hsa-miR-501-3p and hsa-miR-100-5p – were validated by RT-qPCR. The identification of target genes was extracted from miRTarBase and mitoXplorer database. We also performed receiver operating characteristic (ROC) curves and miRNAs that had an AUC > 0.85 were considered potential biomarkers. Results Overall, 41 miRNAs were differentially expressed in T1DM patients compared to control. Hsa-miR-21-5p had the highest number of predicted target genes and was associated with several pathways, including insulin signaling and apoptosis. 34.1% (14/41) of the differentially expressed miRNAs also targeted mitochondrial genes, and 80.5% (33/41) of them targeted nuclear genes involved in the mitochondrial metabolism. All five validated miRNAs were upregulated in T1DM. Among them, hsa-miR-26b-5p showed AUC>0.85, being suggested as potential biomarker to T1DM. Conclusion Our results demonstrated 41 DE miRNAs that had a great accuracy in discriminating T1DM and control group. Furthermore, we demonstrate the influence of these miRNAs on numerous metabolic pathways, including mitochondrial metabolism. Hsa-miR-26b-5p and hsa-miR-21-5p were highlighted in our results, possibly acting on nuclear and mitochondrial dysfunction and, subsequently, T1DM dysregulation.